Arginase 1 of myeloid cells accounts for disease chronicity in Leishmania mexicana-infected mice - Rai, Baplu; Debus, Andrea; Liang Chunguang; Kunz, Meik; Rauh, Manfred; Bogdan, Christian; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Experimental Cutaneous Leishmaniasis: Mouse Models for Resolution of Inflammation Versus Chronicity of Disease - Bogdan, Christian; Debus, Andrea; Sebald, Heidi; Rai, Baplu; Schäfer, Johanna; Obermeyer, Stephanie; Schleicher, Ulrike (Leishmania, 2019)
Experimental cutaneous leishmaniasis of mice is a valuable model to study the immune response to the protozoan pathogen Leishmania and to define mechanisms of parasite control and resolution of inflammation as well as of parasite evasion and chronicity of disease. In addition, over many years Leishmania-infected mice have been successfully used to analyze the function of newly discovered immune cell types, transcription factors, cytokines, and effector mechanisms in vivo. In this chapter we present detailed protocols for the culture, propagation, and inoculation of Leishmania promastigotes, the monitoring of the course of cutaneous infection, the determination of the tissue parasite burden and for the phenotyping of the ensuing immune response. The focus lies on the L. major mouse model, but an overview on other established models of murine cutaneous leishmaniasis is also provided.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cutaneous leishmaniasis; Leishmania major; Mouse models

Resolution of Cutaneous Leishmaniasis and Persistence of Leishmania major in the Absence of Arginase 1 - Paduch, Katrin; Debus, Andrea; Rai, Baplu; Schleicher, Ulrike; Bogdan, Christian (Journal of Immunology, 2019)
Arginase (Arg) 1 is expressed by hematopoietic (e.g., macrophages) and nonhematopoietic cells (e.g., endothelial cells) and converts L-arginine into ornithine and urea. The enzyme is implicated in tissue repair but also antagonizes the production of NO by type 2 NO synthase in myeloid cells and thereby impedes the control of intracellular parasites such as Leishmania major. In this study, we tested whether Arg1 is required for spontaneous healing of acute cutaneous leishmaniasis in C57BL/6 mice and for lifelong parasite persistence in draining lymph nodes (dLNs) of healed mice. In vitro, bone marrow-derived macrophages and lymphoid endothelial cells readily expressed Arg1 in response to IL-4 and/or IL-13, whereas skin or dLN fibroblasts failed to do so, even during hypoxia. In vivo, Arg1 was found in skin lesions and, to a much lower extent, also in dLNs of acutely infected C57BL/6 mice but became undetectable at both sites after healing. Deletion of Arg1 in hematopoietic and endothelial cells using Tie2Cre(+/-) Arg1(fl/fl) C57BL/6 mice abolished the expression of Arg1 in skin lesions and dLNs but did not affect development and resolution of skin lesions, parasite burden, NO production, or host cell tropism of L. major during the acute or persistent phase of infection. Similar to wild-type controls, parasites persisting in Arg1-deficient mice favored NO synthase 2-negative areas and mainly resided in myeloid cells and fibroblasts. We conclude that Arg1 expression by hematopoietic and endothelial cells is completely dispensable for clinical resolution of cutaneous leishmaniasis and for long-term persistence of L. major.
CRIS-Team WoS Importer:2019-03-06

The immunomicrotope of Leishmania control and persistence - Bogdan, Christian; islam, Noor-A-kasida; Barinberg, David; Soulat, Didier; Schleicher, Ulrike; Rai, Baplu (Trends in Parasitology, 2024)
Leishmania is an intracellular protozoan transmitted by sand fly vectors; it causes cutaneous, mucocutaneous, or visceral disease. Its growth and survival are impeded by type 1 T helper cell responses, which entail interferon (IFN)-γ-mediated macrophage activation. Leishmania partially escapes this host defense by triggering immune cell and cytokine responses that favor parasite replication rather than killing. Novel methods for in situ analyses have revealed that the pathways of immune control and microbial evasion are strongly influenced by the tissue context, the micro milieu factors, and the metabolism at the site of infection, which we collectively term the ‘immunomicrotope’. Understanding the components and the impact of the immunomicrotope will enable the development of novel strategies for the treatment of chronic leishmaniasis.
CRIS-Team Scopus Importer:2024-09-13
Keywords: evasion; immunity; Leishmania parasites; leishmaniasis; micro milieu factors; persistence